2-Absorbing Semiprimary Fuzzy Ideal of Commutative Rings - Deniz Sönmez; Gürsel Yeşilot; Serkan Onar; Bayram Ali Ersoy (Journal of Mathematical Sciences and Modelling, 2019)
In this work, we introduce the notion of 2-absorbing semiprimary fuzzy ideal which is a generalization of semiprimary fuzzy ideal. Let $ R $ be a ring. Then the nonconstant fuzzy ideal $ μ $ is called a 2-absorbing semiprimary fuzzy ideal if $ \sqrt{μ } $ is a 2-absorbing fuzzy ideal of $ R $. Furthermore, we give some fundamental results concerning these notions.